JOB ANALYSIS EFFORTS TO IMPROVE HUMAN RESOURCES IN EDUCATION - Aldiana Prestisya; Rr. Amanda Pasca Rini (INCARE, International Journal of Educational Resources, 2023)
Anajab or job analysis is part of human resource management in an organization. Job analysis is a determination that includes, duties, responsibilities, authorities, work relations, work risks, work environment, work equipment, work experience, knowledge and expertise, and competence. This study aims to find out how important job analysis is in improving the quality of human resources. The method used in this research is descriptive qualitative by conducting interviews, observing, and giving questionnaires to respondents. The results of the research found that there were differences between the previous analysis and after the evaluation was carried out, which made it easier for office holders to clearly carry out their work.